2014
DOI: 10.1186/1475-2891-13-112
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of eicosapentaenoic acid is associated with cognitive function in patients with coronary artery disease

Abstract: Background: Recent studies have shown that intake of n-3 polyunsaturated fatty acids (PUFAs) is associated with reduced risk of cognitive impairment and coronary artery disease (CAD); however, it is currently unknown whether reduced serum n-3 PUFA is associated with cognitive impairment in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 24 publications
6
24
0
Order By: Relevance
“…The levels of DHA, EPA and EPA/AA ratio found in our cohort were similar to those found in several other Japanese studies; however our cohort’s AA levels were higher in comparison [42, 43]. For example, in Yanagisawa et al’s study, the mean level of serum DHA was 123.2 ± 27.0 μg/ml, EPA was 81.9 ± 31.1 μg/ml, AA was 119.8 ± 22.7 μg/ml, and EPA/AA ratio was 0.68 ± 0.22 among those aged 65 and older.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The levels of DHA, EPA and EPA/AA ratio found in our cohort were similar to those found in several other Japanese studies; however our cohort’s AA levels were higher in comparison [42, 43]. For example, in Yanagisawa et al’s study, the mean level of serum DHA was 123.2 ± 27.0 μg/ml, EPA was 81.9 ± 31.1 μg/ml, AA was 119.8 ± 22.7 μg/ml, and EPA/AA ratio was 0.68 ± 0.22 among those aged 65 and older.…”
Section: Discussionsupporting
confidence: 90%
“…Bowman et al [10, 43] found significant associations between executive function and DHA as well as EPA. We did not find any associations between EPA, DHA and executive function.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, benefits for the brain that may have been conferred through the effects of EPA on peripheral and/or cerebral blood flow cannot be ruled out. 70 Similarly, the significant effects of diet on 18:2n -6, 22:4n -6, 22:5n -3, and 22:5n -6 are consistent with previous dietary work showing that omega-3 intake regulates the fatty acid desaturase system in a manner that results in these four fatty acids serving as precursor pools or less optimal replacements for arachidonic acid or DHA. 58,59,71,72 Indeed, it may be that alteration of the efficiency of the desaturase system by a singlenucleotide polymorphism may ultimately affect how well a human responds to DHA or omega-3 administration.…”
Section: Discussionsupporting
confidence: 88%
“…In patients with cardiovascular disease, low serum level of EPA and low EPA/AA ratio have been reported to serve as risk factors for cognitive impairment. 6 When taken together with the previous report of a significant association between the severity of leukoaraiosis and decreased cognitive functions, the results of the present study suggest that low serum EPA level will compromise the cognitive function mediated by WMH. 7,8 Furthermore, considering the report that a low serum EPA level is a risk factor for intracerebral hemorrhage, 9 and that the presence of WMH is also one of the risk factors for intracerebral hemorrhage, 10,11 it is assumed that low serum EPA is associated with greater WMH and serves as a risk factor for intracerebral hemorrhage.…”
Section: Discussionsupporting
confidence: 81%
“…In patients with cardiovascular disease, low serum level of EPA and low EPA/AA ratio have been reported to serve as risk factors for cognitive impairment . When taken together with the previous report of a significant association between the severity of leukoaraiosis and decreased cognitive functions, the results of the present study suggest that low serum EPA level will compromise the cognitive function mediated by WMH …”
Section: Discussionsupporting
confidence: 72%